2013
DOI: 10.4172/2155-9600.1000241
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Production System on Quality Indices Distribution in Butterhead Lettuce: A Comparative Study among Open Field and Greenhouse

Abstract: Butterhead lettuce quality was followed through changes in physical, physiological, microbiological, nutritional and sensory indices during postharvest storage. Production was in greenhouses, traditional and mulch, and in the field. Greenhouse lettuce heads had higher nutritional and sensory quality at harvest and lower enzymatic browning. Increased exposure to environmental conditions for open field grown lettuce heads may initiate defense mechanisms that could affect texture, color and appearance. During ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Although many advantages have been attributed to the use of greenhouses to produce leafy greens, it is known that greenhouse leafy greens are usually more susceptible to pests and mechanical damage. However, Goñi et al (2013) reported that greenhouse lettuce heads had higher nutritional and sensory quality at harvest and lower enzymatic browning than open field grown lettuce heads. As in open field systems, soil and soil-less cultivation can be found in greenhouses.…”
Section: Greenhouse Productionmentioning
confidence: 99%
“…Although many advantages have been attributed to the use of greenhouses to produce leafy greens, it is known that greenhouse leafy greens are usually more susceptible to pests and mechanical damage. However, Goñi et al (2013) reported that greenhouse lettuce heads had higher nutritional and sensory quality at harvest and lower enzymatic browning than open field grown lettuce heads. As in open field systems, soil and soil-less cultivation can be found in greenhouses.…”
Section: Greenhouse Productionmentioning
confidence: 99%